A secreted Tapasin isoform impairs cytotoxic T lymphocyte recognition by disrupting exogenous MHC class I antigen presentation - Seipp, Robyn P.; Hoeffel, Guillaume; Moise, Alexander R.; Lok, Siri; Ripoche, Anne-Claire; Marañón, Concepción; Hosmalin, Anne; Jefferies, Wilfred A. (Frontiers in Immunology, 2025)
Endogenous and exogenous antigen processing and presentation through the MHC class I peptide-loading complex (PLC) are essential for initiating cytotoxic T lymphocyte responses against pathogens and tumors. Tapasin, a key component of the PLC, is produced in multiple isoforms through alternative splicing, each isoform influencing the assembly and stability of MHC class I molecules differently. While the canonical Tapasin isoform plays a critical role in stabilizing MHC class I by facilitating optimal peptide loading in the endoplasmic reticulum (ER), the other isoforms function in distinct ways that impact immune regulation. This study aimed to investigate the role of Tapasin isoforms, particularly soluble isoform 3, in modulating antigen presentation and immune responses, focusing on their effects on MHC class I peptide loading and surface expression. Our findings show that isoforms 1 and 2 stabilize TAP and facilitate efficient peptide loading onto MHC class I in the ER, promoting optimal antigen presentation. In contrast, isoform 3, which lacks both the ER retention signal and the transmembrane domain, is secreted and acts as a negative regulator. Isoform 3 inhibits the loading of exogenous peptides onto MHC class I molecules at the cell surface, thereby playing a critical role in the spatial and temporal regulation of MHC class I antigen presentation. The secreted Tapasin isoform 3 likely regulates immune responses by preventing inappropriate T cell activation and cytotoxicity, which could otherwise lead to immune-mediated tissue damage and contribute to autoimmune disorders. Understanding the distinct functions of Tapasin isoforms provides insights into immune regulation and highlights the importance of fine-tuning peptide-loading processes to ensure proper immune responses and prevent immune-related pathologies.